Code-Mixing in Gus Baha's Virtual Da'wah: Linguistic Forms and Communicative Functions - Zultiyanti Zultiyanti; Sutrisno Gustiraja Alfarizi; Gatot Sarmidi (JOLLT Journal of Languages and Language Teaching, 2026)
In digital da'wah, the strategic use of multiple languages has become increasingly significant for conveying religious messages effectively. However, previous studies have primarily emphasized the structural classification of code-mixing, while its communicative functions and sociolinguistic significance in virtual religious discourse remain underexplored. This study aims to analyze code-mixing practices in Gus Baha's virtual da'wah by examining their linguistic forms and communicative functions from a sociolinguistic perspective. This study employed a qualitative descriptive-interpretive approach. The data consisted of verbal utterances extracted from four Gus Baha da'wah videos published on YouTube. The data were transcribed verbatim and collected through observation, note-taking, and recording techniques. They were subsequently analyzed using an interactive model involving data reduction, categorization, contextual analysis, and interpretation. The findings reveal that word-level code-mixing is the predominant linguistic form. In terms of variation, internal code-mixing involving Javanese occurs most frequently, while external code-mixing involving Arabic is mainly employed to express religious concepts and scriptural references. Functionally, code-mixing serves as a strategy for emphasis, clarification, religious expression, and the construction of social intimacy between the preacher and the audience. These findings demonstrate that code-mixing is systematically employed as an adaptive communicative strategy to enhance the effectiveness of digital da'wah. The study contributes to sociolinguistic scholarship by extending the understanding of code-mixing beyond its structural forms to its communicative functions in digital religious discourse and provides insights for developing more audience-oriented communication strategies in contemporary online da'wah.